Analysis of the study sample of patients and their use of antihypertensive drugs in monotherapy - Tetiana Nehoda (Journal of Global Pharma Technology, 2020)
Introduction: Cardiovascular diseases are the primary socio-medical problem of the industrialized countries of the world. One of the most important in terms of increasing life expectancy and the preservation of the viability and quality of life is the solution to the question of the proper therapy of cardiovascular diseases and their timely prevention. The purpose of this study was to determining the structure of patients' use of antihypertensive drugs, as well as to study the subjective factual and prognostic assessment of patients' effectiveness of treatment. Materials and methods: Methods such as: questionnaires of patients (content analysis of case histories) were used. Data processing was performed using statistical and mathematical methods and graphical analysis. Results and discussion: There were some patterns of lowering blood pressure in patients on the background of monotherapy of hypertension and patients following the doctor's instructions for treatment. Conclusions: As a result of the study, it was found that most patients follow the recommendations of doctors on the appointment of antihypertensive drugs.